Evening Primrose Oil Ameliorates Hyperleptinemia and Reproductive Hormone Disturbances in Obese Female Rats: Impact on Estrus Cyclicity - Atteia, Hebatallah H.; Alzahrani, Sharifa; El-Sherbeeny, Nagla A.; Youssef, Amal M.; Farag, Noha E.; Mehanna, Eman T.; Elhawary, Reda; Ibrahim, Gehan A.; Elmistekawy, Amr; Zaitone, Sawsan A. (Frontiers in Endocrinology, 2020)
Obesity is a public health burden disturbing all body functions and reproductive hormones. As obesity increases among females, there will be a rising challenge to physicians in care from fertility problems. Evening primrose oil (EPR oil) contains essential fatty acids including omega-6 linoleic acid with strong anti-inflammatory activity. Since EPR oil has utility in alleviating dysmenorrhea, this study aimed to ascertain its modulatory effect on systemic inflammation, reproductive hormones and estrus cycle irregularity in female obese rats. Thirty-two female rats were distributed to 4 groups: (i) normal, (ii) dietary obese-control female rats and (iii&iv) dietary obese female rats treated with EPR oil (5 or 10 g/kg). Rats were examined for estrus regularity by taking vaginal smears daily during the last 2 weeks of the experiment. Serum level of insulin, leptin, adiponectin and inflammatory cytokines was measured. In addition, serum lipid profile and liver enzyme activities were estimated Adipose tissues were taken for histopathologic examination as well as determination of gene expression for leptin, leptin receptors, adiponectin and visfatin. Obese rats exhibited significant weight gain (90.69±8.9), irregular prolonged estrus cycles (83.33%), increased serum levels of insulin, leptin, prolactin and testosterone and decreased gonadotropin levels. EPR oil exhibited a curative effect on obesity-related irregularity in estrus cycle and ovarian pathology. The underlying molecular mechanism may be related to reduction of systemic inflammation, alleviating insulin resistance and modulation of adipokine expression. EPR oil may be considered as a promising therapeutic intervention against obesity-related female hormonal disturbances and estrus irregularity.